Gastric wall perforation secondary to presumed aspergillosis in a pediatric patient with aplastic anemia: A case report - Reyna-Figueroa, Jesus; Luna-Aguilar, Francisco Javier; Cardoso-Yah, Gabriela; Rivera-Salgado, Maria Irene; Limon-Rojas, Ana Elena; Galindo-Delgado, Patricia (The Journal of Infection in Developing Countries, 2015)
Aspergillosis is an opportunistic fungal infection that may develop in immunocompromised patients with conditions such as leukemia or aplastic anemia. A rare case of stomach perforation following acute fungal gastritis in a 13-year-old female patient with aplastic anemia is reported herein. The patient had developed aplastic anemia without bone marrow fibrosis secondary to acute lymphoblastic leukemia and chemotherapy. The pathological examination revealed a large ischemic transmural perforation (9.5 × 9 cm) associated with fungal septic emboli. Fungal hyphae characteristics were compatible with those of Aspergillus spp. There are few reports identifying fungi as agents associated with gastric perforation. There is a need for early identification of the infectious agent.